SPEAKING KANURI BLANG PADA MASYARAKAT TANI UNTUK KETAHANAN PANGAN DI KECAMATAN SAMATIGA KABUPATEN ACEH BARAT - Khori Suci Maifianti (Universitas Teuku Umar, 2018)
Purpose- SPEAKING Kanuri Blang descripsi the farming community for food security in West Aceh district Samatiga. Methodology- To obtain maximum results with the study researchers used a qualitative approach and using ethnographic methods of communication. Where data collection using direct observation, in-depth interviews and focus group discussions (FGDs). Results - SPEAKING Kanuri Blang in Samatiga Regency si depending on the communication activities undertaken in the implementation of Kanuri Blang. Therefore, Kanuri Blang concluded as the media once the messenger who was instrumental in uniform the farming community in growing rice. Kanuri Blang is important and more powerful than the message in Blang Kanuri own.